Rattan Species Inventory in Rawa Singkil Region of Conservation Forest Management Unit Area - Syam, Nasrianti; Siregar, Mawaddah Putri Arisma; Kusumawardani, Eva Flourentina; Harahap, Laila Apriani Hasanah; Fadilah, Mardi; Saputra, Firman Firdauz; Siahaan, Perry Boy Chandra (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2023)
Rawa Singkil region of Conservation Forest Management Area (KPHK) is a sanctuary for fauna teeming with an abundance of plant species. The species diversity is predominantly constituted of rattan and other non-timber forest products. This investigation seeks to compile a list of the various species of rattan found in the Rawa Singkil KPHK region. Therefore, thisÂ study was carried out in the Rawa Singkil region of KPHK were located in the Aceh Singkil Regency of Aceh Province, Indonesia. Spanning an area of 82,374 ha, this territory comprises nearly fifty percent peat ecosystem. A survey is utilized as the research strategy, with data acquisition conducted via sampling techniques. Moreover, the acquired data were subjected to descriptive analysis on the basis of morphological attributes, encompassing the following morphological characteristics: 1) the stem (including characteristics such as height, diameter, color, internode length, and thorn shape); 2) the leaf, including its length, ocrea, leaf count, leaf color, and leaf surface; 3) knee (color and outline of the knee); 4) thorn; (spine color, length of longest spines, position of spines, and length of shortest spines). Eight species of rattan were discovered in this region, i.e Plectocomia elongata Mart., Daemonorops mattanensis Becc, Daemonorops melanochaetes, Korthalsia echinometra Becc, and Calamus ornatus Blume